PEMBELAJARAN SEJARAH KEBUDAYAAN ISLAM (SKI) DI MTS DARUR ROJA DEPOK - Ahmad Wafi; Aldi Wijaya; Ega Jati Damara; Heru Nugroho; Rio Setiawan; Sofyan Ari Saputra; Rachmy Aulia; Alinda; Muhammad Rizky; Afandy Muharrom; Muhammad Ravito; Nur Aini; Dede Alfiyah Nurhovivah; Siti Shofiyah (J-PAI NIDA EL-ADABI: Jurnal Pendidikan Agama Islam, 2023)
Islamic Religious Education is inextricably linked to Islamic Cultural History (SKI). Students have grown bored with Islamic Cultural History because it is only taught through the traditional lecture method. However, it is different from MTs. Darur Roja, which is in Cinere, Depok, and West Java. Learning the history of Islamic culture has become one of the students' favorite subjects. The purpose of this study was to find out how the Islamic Cultural History subject was taught at MTs Daarur Roja in Depok, West Java. The research method used is field research with a quantitative approach. The results of this study are: 1) Islamic Cultural History at MTs. Darur Roja Depok is a fun lesson; 2) The Islamic Cultural History Subject at MTs. Darur Roja Depok uses varied methods in accordance with the material presented, although it tends to often use expository methods and role play. 3) The supporting factors in the learning process of Islamic Cultural History at MTs Darur Roja Depok are that most of the students are very happy with stories from the past. 4) The inhibiting factors in the learning process of Islamic Cultural History at MTs Darur Roja Depok are that students who are used to online learning must adapt back to offline learning.